Characterisation of large diameter through-thickness metallic pins in composites - Neale, Geoffrey; Saaran, Vinodhen; Dahale, Monali; Skordos, Alexandros A. (Cranfield University, 2022)
Poster and extended abstract presented at the International Conference on Manufacturing of Advanced Composites (ICMAC 2022)
Keywords: Benzoxazine; 'carbon fibre composite'; 'damage mechanics'; pinned; 'Through-thickness reinforcement'